Library Instruction – Not Just for our Users: Skills Upgrading for Librarians as a Way of Increasing Self-Confidence - Daland, Hilde Terese Drivenes (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2015)
This article examines how librarians can improve their skills through a systematic skills upgrading programme, and how this can help improve their confidence in their own expertise. Two identical questionnaires have been issued to the same group of librarians engaged in research support services. In the time period between the two surveys, a skills upgrading programme was carried out. The aim of the second survey is to examine if the librarians’ confidence has increased after the yearlong training programme. Even though one of librarians’ main tasks is searching, research is becoming increasingly interdisciplinary and thusly setting new expectations for librarians.